Analytical study on pyrolyzed products of Desmodesmus sp. cultivated in BG11 - Gang, Li; Fang, Ji; Shunan, Xiang; Yuguang, Zhou; Mengmeng, Jiang; Zhigang, Huang (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Pyrolysis-Gas Chromatography-Mass Spectrometry (Py-GC/MS) was adopted to determine the changes in component of BG11-cultivated Desmodesmus sp. (BG11/8-10) pyrolyzed products at different temperature (300°C-800°C). The results of analysis on a series of total ions chromatogram (TIC) showed that pyrolyzed products of BG11/8-10 at different temperature mainly included aliphatic hydrocarbons, nitrogen compounds, aromatic hydrocarbons, fatty acids, ketones, alcohols, aldehydes and furan compounds. Compared to the bio-oil (42.36%) generated by pyrolysis at 700°C, the relative content of bio-oil generated at 800°C was the highest up to 56.96%. However, higher temperature could easily cause the generation of large quantities of such pollutants as nitrogen compounds and polycyclic aromatic hydrocarbons (PAHs). Therefore, based on lower pollutant discharge and higher bio-oil yield, the optimal pyrolysis temperature of BG11/8-10 was around 700°C.Keywords: Desmodesmus sp., microalgae, pyrolyzed products, pyrolysis temperature, bio-oilDOI: 10.3965/j.ijabe.20171003.2942Citation: Li G, Ji F, Xiang S, Zhou Y G, Jiang M M, Huang Z G. Analytical study on pyrolyzed products of Desmodesmus sp. cultivated in BG11. Int J Agric & Biol Eng, 2017; 10(3): 218–226.